Multiple jejunal perforations in dengue - Jain, Amit Kumar C.; S, Viswanath (International Journal of Advances in Medicine, 2017)
Gastrointestinal perforation is one of the common complications that are associated with high mortality. Stomach, duodenum, ileum and colon are common site of perforation whereas jejunum is an uncommon site for perforation. We report an interesting case of jejunal perforation that occurred in a female patient. To our knowledge, this is the first such isolated case of multiple jejunal perforation in dengue that is being reported in the literature.